Immediate effects of Mulligan mobilization and taping on pain and functional status in patients with knee osteoarthritis - Elbastı, Muhammet Şahin; Yentür, Songül Bağlan (My University, 2025)
Aim: The present study aimed to examine the immediate impact of a physical therapy in combined with mobilization on pain, functional restoration, and decreasing disability in individuals with knee osteoarthritis. Materials and Methods: Pain intensity was evaluated by Visual Analog Scale (VAS), disability by WOMAC Osteoarthritis Index, and function by functional tests. The participants of the study were randomly divided into two groups. The control group received a single session of conventional physical therapy. In contrast, the study group received 3 sets of Mulligan mobilization technique (MWM), one set made up of 10 repetitions in combination to conventional physiotherapy. In the following step, internal rotation taping was applied to the study group. Outcome measurements were repeated after the treatment. Results: A total of 40 patients with knee osteoarthritis were included the study. No significant differences were found between the study and control groups regarding demographic characteristics (p>0.05). Significant changes were observed in all measured parameters within both groups (p<0.05). The pain evaluation showed significant changes among the groups (p=0.002) whereas, no significant differences were identified in functional tests or disability measures (p>0.05). Conclusion: Mulligan MWM technique and internal rotation taping in addition to conventional treatment were found to be more effective in reducing pain compared to the group treated with conventional treatment alone. Adding MWM techn
Keywords: Pain; Osteoarthritis; Taping; Mobilization with movement; Mulligan mobilization